PENGARUH MOTIVASI DAN DISIPLIN TERHADAP KINERJA KARYAWAN PADA SAVERO HOTEL DEPOK - Setyani, Dina; Suhartono, Irwan (Journal of Research and Publication Innovation, 2024)
The purpose of this study was to find out how much influence of Motivation and Discipline have on Employee Performance at Savero Hotel in Depok. The method used is a quantitative method with descriptive analysis. The sampling technique used saturated sampling, where all of the population used as samples in this study totaled 50 respondents. The results of this study are that the motivational variable has a positive effect on employee performance with the results of the t-test value Tcount > Ttable (4.649 <2.011), then HO is rejected and H1 is accepted meaning that there is a significant influence between motivation on employee performance. Discipline has a positive effect on employee performance with the results of the t-test value Tcount > Ttable (2.410 <2.011), then HO is rejected and H2 is accepted meaning that there is a significant influence between discipline on employee performance. Motivation and discipline have a positive effect on employee performance at Savero Hotel in Depok with the regression equation Y = -11.582 + 0.939 X1 + 0.715 X2, the coefficient of determination is 0.648 or 64.8% and the remaining 35.2% is influenced by other factors outside the research variables, the results of the F value are known to show a significance value of 0.000 <0.05, so it is concluded that the first hypothesis in other words motivation and discipline variables simultaneously affect performance employee.